Assessing the Tearing Energy of a Hydrocarbon Elastomeric Seal Material for Fuel Cell Applications. Issue 4 (19th February 2014) - Klein, Justin E.; Singh, Hitendra K.; Divoux, Gilles M.; Case, Scott W.; Dillard, David A.; Dillard, John G.; Moore, Robert B.; Parsons, Jason B.
Abstract Elastomeric gaskets are commonly used between cells within a fuel cell stack to ensure that the reactant gases are isolated. Failure of a fuel cell gasket can cause the reactant gases to mix and can lead to failure of the fuel cell. An investigation of the durability of a hydrocarbon elastomeric seal material developed for proton exchange membrane fuel cells was performed by comparing the tearing energy required for crack propagation of as‐received and environmentally aged samples. Tear force was recorded as a function of crosshead displacement rate and the critical strain energy release rate was calculated and plotted against crack growth rate. Data obtained at different temperatures were then used to generate a fracture energy master curve. Additional samples were aged in selected relevant environments and compared to the as‐received material to study the effect of environmental aging on tear energy master curves. Comparison of tearing energy master curves for different test conditions showed an increase in the tearing energy for all aging environments. The tear energy master curve for testing carried out in water suggested that the crack propagation rates as low as of 10–8 ms–1 can be seen as the fracture energy approaches 80 Jm–2.